2023
DOI: 10.1007/s00535-023-01958-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment escalation and de-escalation decisions in Crohn’s disease: Delphi consensus recommendations from Japan, 2021

Abstract: Background We aimed to develop criteria for treatment intensification in patients with (1) luminal Crohn’s disease (CD), (2) CD with perianal disease and/or fistula, (3) CD with small bowel stenosis, (4) in the postoperative setting, and (5) for discontinuing or reducing the dose of treatment in patients with CD. Methods PubMed and Embase were searched for studies published since 1998 which may be relevant to the five defined topics. Results were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 265 publications
0
2
0
Order By: Relevance
“…Isolated colon involvement was defined as the presence of lesions only in the colon, without any small intestine involvement. The Harvey–Bradshaw Index (HBI) measures clinical disease activity and an HBI score of >4 indicates active disease [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Isolated colon involvement was defined as the presence of lesions only in the colon, without any small intestine involvement. The Harvey–Bradshaw Index (HBI) measures clinical disease activity and an HBI score of >4 indicates active disease [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…18,19 The conflicting results from these RCTs regarding the benefit of TDM in IBD have hindered the widespread adoption of TDM in clinical guidelines (see Tables, Supplemental Digital Content 1, http://links.lww.com/TDM/A735 and http://links.lww.com/ TDM/A736). [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The American Gastroenterological Association conditionally recommended reactive TDM based on very low-quality evidence. 21 The European Crohn's and Colitis Organization guidelines recommend neither proactive nor reactive TDM.…”
Section: Conflicting Evidence On the Role Of Tdmmentioning
confidence: 99%
“…Endoscopy plays an important role in the management of intestinal disease and allows direct visualization of the narrowing bowel. It is recommended to complete colonoscopy, even if imaging tests, such as MRE, are negative, especially when patients have obstructive symptoms, and to perform endoscopic balloon dilatation if necessary 62 . However, before performing video capsule endoscopy, it is recommended to use the patency capsule procedure for ruling out small bowel stenosis 61 .…”
Section: Diagnosismentioning
confidence: 99%
“…Currently, the most commonly used diagnostic methods are magnetic resonance imaging (MRI) and computed tomography (CT) since they are non‐invasive and quickly evaluate active transmural inflammation and detect intestinal strictures (Table 2 ). 50 , 51 , 53 , 54 , 55 , 57 , 59 , 60 , 62 Comparing CT and MRE, a previous study suggested that the latter one is free of ionising radiation and therefore has become the most widely applied method for stricture differentiation. 66 Novel MRI techniques, such as magnetization transfer MRI (MTR) and texture analysis (TA), show promise in assessing intestinal fibrosis.…”
Section: Diagnosismentioning
confidence: 99%